Trichuris trichiura (Linnaeus, 1771) From Human and Non-human Primates: Morphology, Biometry, Host Specificity, Molecular Characterization, and Phylogeny - Rivero, Julia; Cutillas, Cristina; Callejón, Rocío (Frontiers in Veterinary Science, 2021)
Human trichuriasis is a Neglected Tropical Disease, which affects hundreds of millions of persons worldwide. Several studies have reported that non-human primates (NHP) represent important reservoirs for several known zoonotic infectious diseases. In this context, Trichuris infections have been found in a range of NHP species living in natural habitats, including colobus monkeys, macaques, baboons, and chimpanzees. To date, the systematics of the genus Trichuris parasitizing humans and NHP is unclear. During many years, Trichuris trichiura was considered as the whipworm present in humans and primates. Subsequently, molecular studies suggested that Trichuris spp. in humans and NHP represent several species that differ in host specificity. This work examines the current knowledge of T. trichiura and its relationship to whipworm parasites in other primate host species. A phylogenetic hypothesis, based on three mitochondrial genes (cytochrome c oxidase subunit 1, cytochrome b and large subunit rRNA-encoding gene) and two fragments of ribosomal DNA (Internal Transcribed Spacer 1 and 2) allowed us defining a complex of populations of T. trichiura hosting in a large variety of NHP species, in addition to humans. These populations were divided into four phylogenetic groups with a different degree of host specificity. From these data, we carry out a new morphological and biometrical description of Trichuris based on data cited by other authors as well as those provided in this study. The presence of T. trichiura is analyzed in several NHP species in captivity from different garden zoos as possible reservoir of trichuriasis for humans. This study contributes to clarify questions that lead to identification of new taxa and will determine parasite transmission routes between these primates, allowing the implementation of appropriate control and prevention measures.